2020
DOI: 10.1111/emre.12436
|View full text |Cite
|
Sign up to set email alerts
|

Indian Nurses in the United Kingdom: A Two‐Phase Study of the Expatriate‐Host Country National Relationship

Abstract: It is well established that expatriates need support from host country nationals (HCNs) to successfully adjust in their new location, and subsequently perform well in their jobs. Drawing on a sample of 149 Indian nurses in the United Kingdom, this two‐phase study illustrates how expatriate‐HCN interactions unfold over time (two years). To do this, we draw upon social identity theory and show that effective expatriate‐HCN relationship building (i.e., perceived categorization and perceived values similarity) lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 64 publications
0
14
0
Order By: Relevance
“…For instance, the Korean diaspora working in foreign countries intends to stay overseas, while international students studying in Korea are increasingly becoming illegal immigrants. Further, scholars have found that language barriers and unfamiliar social behaviors negatively influence general (nonwork) and interaction (social relationship with Koreans) adjustments (Froese, 2012; Varma, Mathew, Wang, Budhwar, & Katou, 2020; Wang & Varma, 2018, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the Korean diaspora working in foreign countries intends to stay overseas, while international students studying in Korea are increasingly becoming illegal immigrants. Further, scholars have found that language barriers and unfamiliar social behaviors negatively influence general (nonwork) and interaction (social relationship with Koreans) adjustments (Froese, 2012; Varma, Mathew, Wang, Budhwar, & Katou, 2020; Wang & Varma, 2018, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, there is substantial research focusing on destinations attracting a large number of international talent, such as Gulf countries (e.g., Saudi Arabia, Qatar, United Arab Emirates) (Bealer & Bhanugopan, 2014), East Asia (e.g., China, Japan, Korean, Hong Kong, Macau, Singapore) (Froese, 2012;Lo et al, 2012;Peltokorpi, 2008;Stoermer et al, 2020), and Western Europe (Al Ariss & Özbilgin, 2010;Cao et al, 2014;Varma et al, 2021). The proportion of foreigners in the host country might have implications for SIEs' adjustment and work outcomes.…”
Section: Countries Of Destination and Origin In Sie Researchmentioning
confidence: 99%
“…Likewise, there is substantial research focusing on destinations attracting a large number of international talent, such as Gulf countries (e.g., Saudi Arabia, Qatar, United Arab Emirates) (Bealer & Bhanugopan, 2014), East Asia (e.g., China, Japan, Korean, Hong Kong, Macau, Singapore) (Froese, 2012;Peltokorpi, 2008;, and Western Europe (Al Varma et al, 2021). The proportion of foreigners in the host country might have implications for SIEs' adjustment and work outcomes.…”
Section: Countries Of Destination and Origin In Sie Researchmentioning
confidence: 99%